(untitled) (Journal of Forensic Medicine & Toxicology, 2025)
casualties in future and to study the genuine crime rate in the area. Asphyxia causes most of the casualties, which lead to many deaths in the Uttar Kannada district. Objective: To set up a profile of deaths according to demographic details and to know most common cause of death, so that we can direct rigorous efforts to curb their incidence. Materials and Methods: We retrospectively studied the death cases brought for medicolegal autopsy, Karwar Institute of Medical Sciences, Karwar, Uttarakannada, Karnataka, India from the year 2016-2020. During this period, a total of 397 autopsy cases were conducted. Results: Of the total 397 cases, maximum numbers of autopsy cases [94 (23.68%)] were conducted in 2019.Maximum number of autopsy cases [43 (10.83%)] in month of May. Male cases predominated over the female cases, which were 324 (81.61%). The maximum numbers of cases [87 (21.91%)] were in the age group of 21–30 years. Asphyxia related deaths were more in number [179 (45.09%)] of the total cases. Shock and Hemorrhage accounted for 112 (28.21%) cases, Cardiac Failure accounted for 37(9.32%), followed by Respiratory failure [21 (5.96%)] cases. Conclusion: It is observed that the most common cause of death is Asphyxia, probably owing to higher frequency because of coastal area. The most common cause of death among asphyxia death was Drowning.